Distribution and Planning of Tourist Services and Facilities - Jamal Abdel Lteef Ahmad Abdel Haq (My University, 2009)
The aim of this study is to prepare comprehensive evaluations of the city's facilities and services, the planning and distributions of these services between current and past times. The study included an evaluation of the present tourist situations and the difficulties facing the city due to the variety of obstructive factors and offered the possible solutions to overcome problems. For this purpose a review of the old strategies that has been implemented that has affected the tourist industry. The study implemented both the surveying and descriptive methods and used the analytical approach in evaluating the current Palestinians affairs. In addition to the reference guides and the meeting that was conducted with the institutions concerned in this field, the study also gathered its information's using more than 30 related institutions both public and private in order to cover all related factors for the purpose of obtaining the most accurate results. The study confirmed the existence of the right fundamentals for the city to attract tourist as well as the existence of measurable level of security, it has been noted that the tourist and customers prices are relatively low with comparison to other cities in the region. However the study also noted that the city suffer from a lake of a proper infrastructure which in turn affect the public hygiene at the city a missing link between the city's public and private sectors in working to overcome these problems. On the other hand the study found that the single driving factors in promoting the tourist industry at the city were the profits and the financial gains. The lake of advertising and the unavailability of profanes working in this field has affected the industry and above all the occupation and the measures taken by the Israeli authorities has affected the industry most of all. The study concluded that it is vital in order to overcome its problems, the city must consider the suggestions and recommendations that have been founded in addition to that a more comprehensive national approach must be must be adapted in solving these issues. Finally, the study recommended that more attention should be given to this industry and employs enough professionals in this field who have the expertise in international relations' in order to advertise the city in the best possible way in order to achieve the aspirations becoming a world class tourist city.

هدفت هذه الدراسة إلى التعرف على واقع توزيع وتخطيط الخدمات والمرافق السياحية في مدينة أريحا من خلال مراجعة مراحل تطور السياحة في الفترات السابقة وتحليل وتقييم الواقع الحالي للسياحة في منطقة الدراسة. تضمنت الدراسة تقييم الواقع الحالي للسياحة في منطقة أريحا في ظل الظروف القائمة وتحديد المعيقات والصعوبات التي تواجهها، ووضع مقترحات لإستراتيجية مستقبلية من اجل النهوض بمستوى السياحة وتعزيز دورها ومساهمتها في عملية التنمية والتطوير لمنطقة الدراسة. ولتحقيق هدف الدراسة تم الرجوع إلى المفاهيم والنماذج المتعلقة بالسياحة وكذلك الاطلاع على المراحل السابقة لتطور السياحة في مدينة أريحا، واعتمدت الدراسة على المنهج المسحي الوصفي، وكذلك المنهج التحليلي لتقييم الواقع الفلسطيني بالاعتماد على المعلومات والبيانات المتوفرة من مصادر مختلفة، بالإضافة إلى نتائج دليل المقابلة الذي اجري مع كل الجهات ذات العلاقة في منطقة الدراسة والتي بلغ عددها 30 مؤسسة موزعة بين دوائر ومؤسسات في القطاع العام ودوائر ومؤسسات في القطاع الخاص والتي تختص في تنمية وتسويق السياحة في منطقة الدراسة. أشارت نتائج الدراسة إلى وجود عناصر جذب سياحي،ووجود استقرار امني في مدينة أريحا، أيضا أظهرت نتائج الدراسة إلى أن التكلفة الاقتصادية للسياحة في مدينة أريحا رخيصة الثمن، ووجود نقص في الاهتمام بالخدمات الصحية في مجال السياحة، وكذلك ضعف في التنسيق بين المؤسسات الحكومية فيما بينها وبين القطاع الحكومي والقطاع الخاص، من جهة أخرى أظهرت الدراسة إن الربح المادي هو الغاية الكبرى للسياحة في أريحا وأيضا أظهرت الدراسة انه لا يوجد ترويج سياحي خارجي كافي، إضافة إلى نقص في الخبرات البشرية لإدارة السياحة أو العمل بها، ووجود الاحتلال يؤثر سلبا في صناعة السياحة في مدينة أريحا. وقد خلصت الدراسة إلى عدد من التوصيات، أهمها ضرورة تبني الإستراتيجية المقترحة التي تضمنتها الدراسة. كذلك أوصت الدراسة بضرورة صياغة خطة وطنية للسياحة في فلسطين عامة، وفي أريحا خاصة. وأخيراً، أوصت الدراسة إلى ضرورة وجود مختصين في العمل السياحي، وكذلك ضرورة الترويج السياحي الداخلي والخارجي لمنطقة الدراسة.
توزيع وتخطيط الخدمات والمرافق السياحية في مدينة أريحا